(untitled) (Journal of Engineering, 2011)
Curing of concrete is the maintenance of a satisfactory moisture content and temperature for a period of time immediately following placing so the desired properties are developed. Accelerated curing is advantages where early strength gain in concrete is important. The expose of concrete specimens to the accelerated curing conditions which permit the specimens to develop a significant portion of their ultimate strength within a period of time (1-2 days), depends on the method of the curing cycle.Three accelerated curing test methods are adopted in this study. These are warm water, autogenous and proposed test methods. The results of this study has shown good correlation between the accelerated strength especially for the proposal curing test method and normal strength using normal curing method at ages 7 and 28 day for the five different chemical composition of cement with different water to cement ratios equal to 0.45, 0.55, 0.65 and 0.75. Linear and nonlinear regression analysis show high correlation for the different types of the accelerated curing methods with coefficient of correlation (R2) more than 0.9.